The geotourist potential of the Bialka River valley (in the Podhale Basin) – a project of a geotourist trail // Potencjał geoturystyczny doliny Białki (niecka podhalańska). Projekt ścieżki geoturystycznej - Hełdak, Damian (Geotourism/Geoturystyka, 2020)
The Białka valley is located in southern Poland. The middle part of the valley is build-up of the Paleogene Podhale Flysch. In common opinion, this region is not particularly attractive in respect to geotourism. To prove that it is not true, I proposed the project of geotourist trail in this area. The trail comprises 5 geosites, where the most attractive objects (according tothe author) will be presented. These include calcareous tufa in Jurgow (first geosite), faults in the Bukowińska Grapa (second geosite), where pronounced effects of lateral erosion are evident, which lead to the shifting of the river bed. At this geosite there are also visible joints systems in sandstones (third geosite) and the sandstones show various types of lamination. At the fourth geosite, there occur clear neotectonic features revealed by granite boulders deposited several meters above the contemporary riverbed. Finally, at the fifth geosite, one can examine the thermal pools, which are examples of favorable geological conditions utilized for recreational purposes.//Dolina Białki znajduje się w południowej Polsce. Jej środkowa część zbudowana jest z paleogeńskiego fliszu podhalańskiego. Ogólnie uważa się, że obszar zbudowany z tych skał nie jest szczególnie atrakcyjny pod względem geoturystycznym. Aby udowodnić, że jest inaczej, zaproponowano projekt ścieżki geoturystycznej. Ścieżka składa się z pięciu najciekawszych (według autora) stanowisk. Składają się na nie kolejno martwice wapienne w Jurgowie (pierwsze stanowisko), uskoki w obrębie Bukowińskiej Grapy (drugie stanowisko), a także miejsce wyraźnej, lateralnej erozji bocznej, która prowadzi do przesuwania się koryta. Wyraźnie odsłonięte są tutaj ławice piaskowców o różnej laminacji, poprzecinane spękaniami ciosowymi (trzecie stanowisko). Na czwartym stanowisku widoczne są wyraźne dowody na zachodzące tutaj ruchy neotektoniczne (otoczaki granitowe wyniesione kilkanaście metrów nad poziom obecnego koryta), a na ostatnim, piątym stanowisku znajdują się baseny termalne, które są znakomitym przykładem wykorzystania sprzyjającej budowy geologicznej do celów gospodarczych.